SOME EXPERIENCES IN USING NEC2 TO SIMULATE RADIATION FROM SLOTS ON CYLINDERS - Lim, S.H.H (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A numerical method based on use of the NEC2 code has been used to study radiation from a slot in the surface of a conducting cylinder and the results used in a comparison with the eigenfunction series solu-tion. The two cases of an axial and circumferential slot have been taken as representative between them of the more general case of an inclined slot. In the case of a circumferential slot, truncation of the cylin-der to finite length has been found in all cases to lead to numerical and analytic results which are in poor agreement and this has been accounted for with an argument based on the geometrical theory of dif-fraction. However this alone is not enough to explain what is observed with axial slots where, for small cyl-inders, agreement of the two approaches is good but fails for larger cylinders. It is postulated that this is due to excitation of waveguide modes on the inside of the larger cylinders and the result confirmed by clos-ing the ends of the cylinder in the NEC2 model with a system of radial wires, when agreement is again re-stored.